COMPONENTS OF ADEQUACY IN THE ART TRANSLATION (Academicia Globe: Inderscience Research, 2021)
Adequate translation means perfectly reflected content of the original and full stylistic and semantic correspondence. Great importance is attached to the study of the phenomena of literary translation in a comparative-stylistic plan as an effective scientific method. Recreation of style is an inherent problem in literary translation. Equivalence is the defining measure of the quality of any translation. The study of translation transformations is one of the relevant aspects when considering the linguistic features of the texts of works of art. In the process, the created text is transformed into another language system, and the translation is analyzed as a cultural phenomenon. The depicted national flavor in literary translation is very complex in its content. One should strive to present the principles, requirements and means of adequate translation from the point of view of national identity, genre specifics, poetic expression of size, color of the era, as well as preserving the form and content of a work of art.